2016
DOI: 10.1590/1983-21252016v29n225rc
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Tilapia Filleting Waste Meal for Swine in the Nursery Phase

Abstract: -Three experiments were conducted to determine the nutritional composition of tilapia filleting waste meal (TFWM) for pigs in the initial phase. In the first experiment, the chemical composition and the values of digestible and metabolizable energy of TFWM were determined using 10 pigs (15.10 ± 0.74 kg), distributed in cages for metabolic research (2 treatments X 5 replicates). The TFWM replaced 20% of the reference diet based on corn and soybean meal. In the second experiment, the ileal digestibility coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…This is consistent with our finding. Such finding also aligns with that of Richart et al [6], who observed that the consumption of 10% tilapia filleting waste meal by growing pigs (15 to 30 kg BW) did not have any detrimental effects on their growth performance. However, up to 15% of tilapia filleting waste in the diet caused a decrease in final BW, ADG, and ADG.…”
Section: Growth Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with our finding. Such finding also aligns with that of Richart et al [6], who observed that the consumption of 10% tilapia filleting waste meal by growing pigs (15 to 30 kg BW) did not have any detrimental effects on their growth performance. However, up to 15% of tilapia filleting waste in the diet caused a decrease in final BW, ADG, and ADG.…”
Section: Growth Performancesupporting
confidence: 92%
“…However, no reports on dietary PRF supplementation for monogastric animals are available. One relevant report revealed that the inclusion of 20% tilapia (Oreochromis niloticus) filleting waste meal in the diet of growing pigs significantly increased their body weight, average daily gain, and feed efficiency [6]. Regarding the nutritional characteristics of PRF, it can be utilized as a good alternative ingredient for monogastric animals.…”
Section: Introductionmentioning
confidence: 99%
“…When working with the inclusion of 0 to 20% of tilapia filleting waste meal to 15 to 30 kg piglets, Richart et al (2016) observed that up to 10% level did not affect the piglet's final weight and average daily weight gain, however above that level there was a decrease on those variables due to possible amino acids loss, especially lysine during the thermal treatment of the residue.…”
Section: Resultsmentioning
confidence: 98%
“…Dentre eles, destaca-se a farinha de resíduos industriais de filetagem de tilápia (cabeça, espinhas, vísceras, gordura abdominal e barbatanas), que, segundo Richart et al (2016), apresenta, em média, 95,28% de matéria seca, 53,43% de proteína bruta, 16,82% de extrato etéreo, 23,42% de matéria mineral, 6,98% de cálcio e 3,52% de fósforo.…”
Section: Introductionunclassified